Genetic assessment of captive red pandas (Ailurus fulgens) in American zoos to address management separation by putative subspecies. Issue 3 (10th March 2021) - Dueck, Lucy A.
Abstract: Red pandas ( Ailurus fulgens ) are small charismatic mammals native across montane southern Asia, now endangered by human impacts. They are considered "living fossils" as the sole member of a distinct family, warranting higher conservation priority. Therefore, ex situ breeding programs were initiated to prevent extinction and act as genetic reservoirs for reintroduction, although complicated by apparent taxonomic subdivision. This study investigated whether the separation of captive red pandas in the North American Species Survival Plan® by putative subspecies was justified. A 383‐bp segment of mitochondrial DNA control region was therefore sequenced from 67 members representing matriarchal lineages of both groups. A network analysis placed the 11 haplotypes found into separate but closely connected clusters, with one group more strongly related than the other. Statistical analyses and diversity indices corroborated differentiation between the two management units. Phylogenetic analyses employing multiple outgroups confirmed, although not robustly, reciprocal monophyly of the four‐ and seven‐haplotype clades representing putative subspecies Ailurus fulgens fulgens and Ailurus fulgens styani, respectively. These empirical results are adequate to justify continued independent management of these zoo subpopulations, but cannot be definitive for taxonomic classification due to limited sampling from their native range. They will, however, be useful in evaluating long‐term genetic diversity changes, focusing management efforts on newly revealed evolutionary limitations, and comparing with an assessment of wild red pandas to determine how representative zoo populations are for reintroduction purposes. Maintaining genetic diversity and population structure of endangered species is essential to protect evolutionary potential and adaptations for long‐term sustainability. Research Highlight: Red pandas from both subpopulations in American zoos were genotyped using mitochondrial DNA sequencing. Data analyses confirmed that the two groups were genetically different, perhaps at the subspecies level, and should continue to be maintained separately. Abstract : Species Survival Plan® (SSP) red panda genetic clusters